PENGARUH ROA, ROE DAN NPM TERHADAP PERTUMBUHAN LABA PADA PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Agustina, Dwi; Hikmah, Hikmah (SCIENTIA JOURNAL, 2021)
Same as other companies, banking companies are also oriented to make a profit every period. This research aims to determine and analyze the effect of ROA, ROE and NPM on profit growth either simultaneously or partially. The population in this research is in banking companies listed on the Indonesian Stock Exchange for the year 2015-2019. The sample was selected using a purposive sampling method in order to obtain a sample of 23 companies from 45 companies. The variables used in this study are: ROA (X1), ROE (X2), NPM (X3) and Profit Growth (Y). This research uses secondary data in the form of annual financial statements of companies obtained from the Indonesian Stock Exchange. Methods of data analysis using multiple linear regression analysis method with SPSS version 26. The results show partially that ROA has no significant effect on profit growth, ROE has a significant effect on profit growth, and NPM has no significant effect on profit growth. The results of the research show that simultaneously there is a significant influence between ROA, ROE and NPM on the profit growth of banks listed on the Indonesian Stock Exchange in 2015-2019.